Employee Performance of the Lento 3t Cracker Small and Medium Industry in Koto XI Tarusan District, Pesisir Selatan Regency - Astilla, Maylanda; Yulastri, Asmar (Universitas Negeri Padang, 2023)
The background of this research is observation through the results of observing problems that often occur, namely that employee performance is still low when getting lots of lento 3t cracker orders, employees can't fulfill these orders and the results are not in accordance with the goals desired by the industry. there are still many employees who play cellphones while working, such as opening various social media. This causes employees to be ineffective and inefficient in the 3t lento cracker production process. This study aims to describe the performance of employees of the Lento 3t Crackers Small and Medium Industry in Koto XI Tarusan District, Pesisir Selatan Regency.This type of research is descriptive research with a quantitative approach. The population of this study were all employees of the Lento 3t Crackers Small and Medium Industry in Koto XI Tarusan District, Pesisir Selatan Regency, totaling 45 people. The sampling technique uses a saturated sampling technique so that all populations become samples. Data collection techniques were carried out using a questionnaire (questionnaire) with a Likert scale that has been tested for validity and reliability. Furthermore, the data were analyzed through descriptive analysis with the assessment categorization method.The results of the study concluded that the performance of employees of the Lento 3t Crackers Small and Medium Industry in Koto XI Tarusan District, Pesisir Selatan Regency, found that employee performance was 49%, employees belonging to the medium category. So it can be concluded that the employee performance of the employees of the Lento 3t Cracker Small and Medium Industry in Koto XI Tarusan District, Pesisir Selatan Regency is moderate.